Novos compostos de alta dimensionalidade envolvendo um ligante fexível bisfosfinato - Silva, Rubia Mara Siqueira da (2010)
Compounds involving phosphinates ligands possess the ability to form strong metal-oxygen bonds in the solid state by virtue of the very electronegative O atoms bound to an electropositive P atom. This fact was the inspiration to the search of the synthesis and characterization of a new type of ligand bisphosphinate (O2PCH2(C6H4)CH2PO2), PMPP2-, in intention to increase the dimensionality of metallic polymers, as well to understand the interactions between metal centers with this flexible ligand. In this work ten new compounds with high dimensionality were synthesized and characterized. The ligand 1,4-phenylenebis(methylene) bis(phenylphosphinate), abbreviated to H2PMPP 1, was synthesized. In its crystal structure, molecules are linked by intermolecular hydrogen bonds to form a two-dimensional layered supramolecular structure. The crystal structure of the ammonium salt of this ligand (NH4)2PMPP 2, formed a three dimensional structure by hydrogen bonding interactions. From aqueous solutions of compound 2 with corresponding metal acetates, nitrates or chlorides, five new coordination polymers and three ionic supramolecular compounds were synthesized. The coordination compound tectopoly-[ Ag2(μ8-PMPP)] 3 had a three-dimensional structure and was considered isostructural to compound 2. The hydrothermal reaction of H2PMPP with MnCl2×4H2O produced the two-dimensional (2D) coordination polymer phyllo-poly-[Mn2(μ4- PMPP)(μ2-H2PMPP)] 4. The series of coordination compounds involving alkaline earth metals, phyllo-poly-[(Ba(H2O)3)2(μ-H2O)2(μ4-PMPP)](PMPP)] 5 and the isostructural, phyllo-poly[Sr2(H2O)4.25(μ-H2O)(μ4-PMPP)(μ3-PMPP)]×3H2O 6 and phyllo-poly[Ca2(H2O)3.65(μ-H2O)(μ4-PMPP)(μ3-PMPP)]×3H2O 7. In 5, 6 and 7, complex nets of hydrogen bonds between the coordinated water molecules and the PMPP2 ligands link the 2D layers into the three-dimensional framework structures. The ionic compounds derived from Co2+, [Co(H2O)4(NC5H6)2](PMPP), 9, and ([Co(H2O)6](PMPP))·2H2O, 10·2H2O were obtained from the dissolution of [Co(PMPP)] 8, in a solution of water/pyridine and cold water, respectively. The compound ([Ni(H2O)6](PMPP)·2H2O, 11 is isostructural with the structure of the compound 10×2H2O. The ionic compounds form supramolecular species formed by hydrogen bonds. The reversible structural rearrangement of 5, 6, 7, 10·2H2O and 11 frameworks was studied. This new flexible ligand bis(phosphinates) can lead to the formation of flexible and dynamic frameworks. This so called structural dynamism and at present is regarded as the basis of a new class of practical materials. Compounds 5, 6, 7, 10·2H2O and 11 were dehydrated leading to 5D, 6D, 7D, 11D and 8; rehydration converted them to their original species. However, for compounds 6D, 7D, this behavior is not verified. The investigation of the mechanism of hydration/ rehydration was done using X-ray powder diffraction techniques, thermoanalytical methods and infrared spectroscopy.